Coexistence of natural enemies in a multitrophic host-parasitoid system - Bonsall, M; Hassell, M; Reader, P; Jones, T (2004)
1. This study explored the temporal and spatial aspects of coexistence over many generations in a multispecies host-parasitoid assemblage. 2. The long-term interaction between the cabbage root fly, Delia radicum (Diptera: Anthomyiidae), and two of its natural enemies, Trybliographa rapae (Hymenoptera: Fitigidae) and Aleochara bilineata (Coleoptera: Staphylinidae), in a cultivated field at Silwood Park over 19 years was explored. 3. Although time series showed that the populations were regulated, the impact of the natural enemies was highly variable. Within-year determinants showed that the spatial response of the specialist parasitoid, T. rapae, was predominantly independent of host density while A. bilineata acted simply as a randomly foraging generalist parasitoid. 4. These findings are compared and contrasted with an earlier investigation of the same system when only the first 9 years of the time series were available. This study demonstrated the potential of long-term field studies for exploring hypotheses on population regulation, persistence, and coexistence.